A Split Jewish Diaspora: Its Dramatic Consequences - Edrei, Arye; Mendels, Doron 1944- (2007)
This article proposes that a language divide and two systems of communication have brought to a serious gap between the western Jewish Diaspora and the eastern one. Thus the western Greek-speaking Jews lost touch with the Halakhah and the Rabbis, a condition that had far-reaching consequences on Jewish history thereafter. The Rabbis paid a high price for keeping their Halakhah in oral form, losing in consequence half of their constituency. An oral law did not develop in the western diaspora, whereas the existing eastern one was not translated into Greek. Hence it is not surprising that western Jews contributed nothing to the development of the oral law in the east. The Jewish communities that were isolated from the Rabbinic network served as a receptive basis for the development of an alternative Christian network by Paul and the apostles, which enabled it to spread throughout the Mediterranean basin. The Jews that remained ‘biblical’ surfaced in Europe in the Middle Ages.
Keywords: systems of communication; language divide; Land of Israel; western diaspora; Eastern diaspora